Meiotic Chromosome Dynamics in Zebrafish - Imai, Yukiko; Olaya, Ivan; Sakai, Noriyoshi; Burgess, Sean M. (Frontiers in Cell and Developmental Biology, 2021)
Recent studies in zebrafish have revealed key features of meiotic chromosome dynamics, including clustering of telomeres in the bouquet configuration, biogenesis of chromosome axis structures, and the assembly and disassembly of the synaptonemal complex that aligns homologs end-to-end. The telomere bouquet stage is especially pronounced in zebrafish meiosis and sub-telomeric regions play key roles in mediating pairing and homologous recombination. In this review, we discuss the temporal progression of these events in meiosis prophase I and highlight the roles of proteins associated with meiotic chromosome architecture in homologous recombination. Finally, we discuss the interplay between meiotic mutants and gonadal sex differentiation and future research directions to study meiosis in living cells, including cell culture.